Evaluation of Village Funding Policy in Kampung Mekurima, Kwamki Narama District Mimika Regency - Dorthea Renyaan (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this study was to describe and analyze the impact of the Village Fund Management policy implemented in Mekurima Village, Kwamki Narama District, Mimika Regency, whether it had achieved its goals, what is the accountability of public implementers to Village Fund policies, and provide input on Village Fund policies in Mekurima Village, Kwamki District The name of Mimika Regency in the future. This study uses a qualitative descriptive approach by describing problems and phenomena to explore and explore and explain the Implementation of Village Fund Management that has been implemented, which is then analyzed qualitatively. However, the process is still not optimal because there are still obstacles related to the availability of Human Resources (HR) managing Village Funds that still need to be adequately prepared. Therefore, the thing that will be of concern in the future is the need for skills training facilities for the community to utilize the potential of human resources in the Village so that they are more independent in managing the Village Fund.